Hubungan Masa Kerja, Pengawasan Dengan Perilaku Tidak Aman Pekerja Operasional PT. Bumi Jasa Utama - Iffat Nurjihan Labibah; A. Rizki Amelia AP; Nurmiati Muchlis (Window of Public Health Journal, 2026)
Unsafe behavior is one factor that can cause workplace accidents. Factors that influence unsafe behavior in workers need to be studied to support work accident prevention efforts. This study aims to determine the relationships between work period and supervision and unsafe behavior among operational workers at PT Bumi Jasa Utama. This study uses a quantitative, cross-sectional design. The population in this study comprised all operational workers at PT Bumi Jasa Utama, and a sample of 51 respondents was selected using a total sampling technique. Data were collected through questionnaires and analyzed using univariate and bivariate analysis with the Chi-Square test at a 95% confidence level (α = 0.05). The results showed that most respondents had a new work period (62.7%), supervision was in the inadequate category (52.9%), and they engaged in unsafe behavior (72.5%). The bivariate analysis showed that work period did not have a significant relationship with unsafe behavior among operational workers at PT Bumi Jasa Utama (p = 0.266). Meanwhile, supervision showed a significant relationship with unsafe behavior (p-value = 0.052, Chi-Square test). This study concluded that supervision was associated with unsafe behavior among PT Bumi Jasa Utama's operational workers, whereas tenure was not significantly associated. Therefore, the company is expected to improve supervision of occupational safety and health (OHS) implementation to minimize unsafe behavior and prevent workplace accidents.